2018
DOI: 10.1590/1678-5150-pvb-5413
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação morfofuncional do corpo lúteo para diagnóstico precoce de gestação 20 dias após IATF em vacas mestiças leiteiras

Abstract: RESUMO: A detecção superprecoce de gestação é de grande relevância quando se trata do aumento da produtividade dos rebanhos, na tentativa de redução do tempo de serviço desses animais. Por tal relevância, objetivou-se utilizar a ultrassonografia (US) Doppler como ferramenta para predição de gestação, avaliando a irrigação do corpo lúteo (CL), vinte dias após IATF. Setenta e três vacas mestiças foram avaliadas 20 dias após IATF por US transretal. Para obtenção do diâmetro do CL (DCL) e sua área (ACL) utilizou-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…In non-pregnant women, this cavity tends to disappear with the estrus cycle. Silva et al (2018) studied the relationship between ovulatory follicle diameter, CL area, and pregnancy rate in beef cows submitted to FTAI and obtained a luteal body with a mean area of 2.04±0,22cm² in the group of pregnant females, similar to the rate observed in this study; these values are similar than those obtained in the present study. Silveira et al (2012) used Nelore cows synchronized for FTAI and reported pregnancy rates of 53%; in addition, Tortorella et al (2013) used 400 IU of eCG in the FTAI protocol for beef cows to evaluate the effect on gestation rate, among other variables, and obtained a 52% pregnancy rate for a group of treated females.…”
Section: Resultssupporting
confidence: 88%
“…In non-pregnant women, this cavity tends to disappear with the estrus cycle. Silva et al (2018) studied the relationship between ovulatory follicle diameter, CL area, and pregnancy rate in beef cows submitted to FTAI and obtained a luteal body with a mean area of 2.04±0,22cm² in the group of pregnant females, similar to the rate observed in this study; these values are similar than those obtained in the present study. Silveira et al (2012) used Nelore cows synchronized for FTAI and reported pregnancy rates of 53%; in addition, Tortorella et al (2013) used 400 IU of eCG in the FTAI protocol for beef cows to evaluate the effect on gestation rate, among other variables, and obtained a 52% pregnancy rate for a group of treated females.…”
Section: Resultssupporting
confidence: 88%
“…Em estudos similares, observou-se a influência do comportamento de estro sobre as dimensões luteais e os níveis séricos de progesterona no período pós-ovulatório, sugerindo, assim, a existência de uma correlação entre expressão do estro e parâmetros morfofuncionais luteais [34,35,43]. Deste modo, a mensuração da vascularização, nesta estrutura ovariana, pode fornecer importantes informações sobre a função luteal e o índice de fertilidade em fêmeas bovinas [8,12,28,48].…”
Section: Discussionunclassified